Soil-cement for high-velocity spillway flow applications - Kadrmas, Korey J., author; Huzjak, Robert J., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
Although soil-cement has been used on many dams for slope erosion protection for over 50 years, soil-cement has had limited use as an overtopping liner protection for spillways. The application of soil-cement for a spillway liner was researched and modeled to establish performance criteria to support design of an auxiliary spillway for a new large, high hazard dam in Colorado. Case studies were researched and hydraulic performance tests were conducted at the Hydraulics Laboratory at the Engineering Research Center of Colorado State University (CSU) to establish design criteria for soil-cement lined spillways subject to high-velocity flows. The purpose of this paper is to supplement the existing base of research regarding the suitability of soil-cement for hard protection channel lining applications subject to high-velocity flow. Information in this paper was developed from a special application testing program developed for an emergency spillway for a dam in Colorado. The paper will include the methods and procedures of batching and placing the soil-cement specimens, a summary of data collected, results, and conclusions for the soil-cement performance testing program.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: soil-cement; high-velocity; spillway; overtopping; protection